Customs, Domestic Market and Commercial Elite in Cusco Before and After the Great Rebellion of 1780 - O'Phelan Godoy, Scarlett (Universidad del Pacífico, 1986)
​The present article focuses on five of the most prominent merchants in Cusco during the late eighteenth century. All of them had some common features, namely their penninsular origins and their investments in sugar cañe and native textiles. They all supplied the Upper Peruvian market and provided commodities for the corregidor's reparto. It might be observed that the Bourbon Reforms -at the fiscal level- affected their interests profoundly, as well as did the Great Rebellion of 1780-81.